2022
DOI: 10.1136/heartjnl-2022-321754
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings and prognostic values in patients hospitalised with COVID-19 in the World Heart Federation Global Study

Abstract: BackgroundCOVID-19 affects the cardiovascular system and ECG abnormalities may be associated with worse prognosis. We evaluated the prognostic value of ECG abnormalities in individuals with COVID-19.MethodsMulticentre cohort study with adults hospitalised with COVID-19 from 40 hospitals across 23 countries. Patients were followed-up from admission until 30 days. ECG were obtained at each participating site and coded according to the Minnesota coding criteria. The primary outcome was defined as death from any c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…It is speculated that the possible reasons are direct myocardial injury caused by viral damage and cytokine storm, indirect endothelial injury, disruption of the renal angiotensin system, and pressure induced arrhythmia The activation of the sympathetic nervous system and the weakening of the vagus nerve's impact on the heart caused by the virus itself and in ammatory cytokine response lead to severe autonomic nervous system imbalance. After adjusting for multiple factors, sinus tachycardia (>120 bpm) was found to be an independent risk factor for in-hospital mortality, cardiovascular events, and ICU occupancy rate [17]. These studies also obtain the heart rate increase after COVID-19 infection through cross-sectional study or setting up a control group, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 89%
“…It is speculated that the possible reasons are direct myocardial injury caused by viral damage and cytokine storm, indirect endothelial injury, disruption of the renal angiotensin system, and pressure induced arrhythmia The activation of the sympathetic nervous system and the weakening of the vagus nerve's impact on the heart caused by the virus itself and in ammatory cytokine response lead to severe autonomic nervous system imbalance. After adjusting for multiple factors, sinus tachycardia (>120 bpm) was found to be an independent risk factor for in-hospital mortality, cardiovascular events, and ICU occupancy rate [17]. These studies also obtain the heart rate increase after COVID-19 infection through cross-sectional study or setting up a control group, which is consistent with our study.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous observational studies and case reports have suggested a potential link between COVID-19 and the prolongation of the QT interval on ECG 4,8,[13][14][15][20][21][22]35,36 . To address the limitations of confounding factors and reverse causality inherent in observational research 27 , we conducted an MR analysis to investigate whether COVID-19 has a genetic causal impact on QT interval changes.…”
Section: Discussionmentioning
confidence: 99%
“…ECG serves as an essential tool in managing COVID-19 patients, unveiling cardiac involvement such as atrial brillation, prolonged QT intervals, and ventricular and supraventricular arrhythmias 19 . Observational studies have indicated an independent association between QT interval prolongation and COVID-19, suggesting that QT interval prolongation may serve as an early prognostic marker for disease progression and mortality 4,8,[13][14][15][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lower heart rate variability on ECG, as a marker of vagal nerve activation, has also been linked to a greater risk of ITU admission and inpatient mortality [274]. A recent large multi‐centre cohort study showed that major ECG abnormalities and sinus tachycardia (>120 beats per minute) were linked to adverse clinical outcomes in COVID‐19 patients [275]. However, certain ECG findings, such as AF, bundle branch block, ischaemic abnormalities and prolonged QTc, were not associated with adverse clinical outcomes in this study [275], which appear to cast doubts over previous data suggesting their prognostic importance [240242, 260262, 268273].…”
Section: Electrocardiogram (Ecg)mentioning
confidence: 99%
“…A recent large multi‐centre cohort study showed that major ECG abnormalities and sinus tachycardia (>120 beats per minute) were linked to adverse clinical outcomes in COVID‐19 patients [275]. However, certain ECG findings, such as AF, bundle branch block, ischaemic abnormalities and prolonged QTc, were not associated with adverse clinical outcomes in this study [275], which appear to cast doubts over previous data suggesting their prognostic importance [240242, 260262, 268273]. The exact mechanisms underlying these differences in observation remain unclear and deserve further investigation.…”
Section: Electrocardiogram (Ecg)mentioning
confidence: 99%